Efektywność w przepisach ustawy o finansach publicznych - Piotr Sokół (Studia i Materiały)
The article discusses the importance of efficiency in the regulations on public finances. The considerations were based on the provisions of the Act of 27 August 2009 on public finances. For the purposes of this article, efficiency has been distinguished in two sections. The first deals with the effectiveness of the public funds management. The second involves the subjective efficiency associated with the functioning of organizational units of the public finance sector.